Gender Differences in the Violence Exposure Types That Predict PTSD and Depression in Adolescents. Issue 17 (September 2021) - Schwartz, Byron; Kaminer, Debra; Hardy, Anneli; Nöthling, Jani; Seedat, Soraya
Both specific forms of violence and polyvictimization have been associated with an increased risk for negative mental health outcomes in youth. Despite evidence of gender differences in trauma experience and impact, gender patterns in the comparative contribution of specific violence exposures versus polyvictimization to mental health outcomes have seldom been explored. The few existing studies have all been conducted in high-income countries, while there is a dearth of research from lower and middle-income countries. This study examined the contribution of witnessed and direct community violence, domestic violence, sexual abuse, and different levels of polyvictimization to the severity of posttraumatic stress disorder (PTSD) and depression in a clinic sample of children and adolescents ( n = 310) in South Africa. Although polyvictimization rates were high across both genders, polyvictimization posed differential risks for boys and girls. For girls, higher levels of polyvictimization, but not individual violence types, predicted both PTSD and depression severity. For boys, polyvictimization did not predict PTSD or depression severity. Higher levels of victimization in the community predicted PTSD severity among boys, while no forms of violence predicted depression. The findings confirm the value of examining gender patterns in the risk for posttraumatic sequelae posed by exposure to specific and cumulative forms of violence. Implications for interventions with youth in high-violence contexts such as South Africa are considered.